2017
DOI: 10.1186/s11689-017-9183-z
|View full text |Cite
|
Sign up to set email alerts
|

Distinct neural bases of disruptive behavior and autism symptom severity in boys with autism spectrum disorder

Abstract: Background: Disruptive behavior in autism spectrum disorder (ASD) is an important clinical problem, but its neural basis remains poorly understood. The current research aims to better understand the neural underpinnings of disruptive behavior in ASD, while addressing whether the neural basis is shared with or separable from that of core ASD symptoms. Methods: Participants consisted of 48 male children and adolescents: 31 ASD (7 had high disruptive behavior) and 17 typically developing (TD) controls, well-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 100 publications
(119 reference statements)
4
46
0
1
Order By: Relevance
“…Anxiety and disruptive behavior were positively correlated in the autism group. Furthermore, the link between disruptive behavior and default mode network activity in the autism group was partially mediated by anxiety symptoms for the anterior cingulate cortex and medial prefrontal cortex [Yang et al, ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anxiety and disruptive behavior were positively correlated in the autism group. Furthermore, the link between disruptive behavior and default mode network activity in the autism group was partially mediated by anxiety symptoms for the anterior cingulate cortex and medial prefrontal cortex [Yang et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…Positive and negative relations between anxiety and amygdala volume [Corbett et al, ; Juranek et al, ], and positive relations between anxiety and amygdala activity [Herrington et al, ; Kleinhans et al, ] have been found. Furthermore, although the work is limited to only three studies, sensory over‐responsivity and disruptive behaviors may play a role in the link between anxiety and brain activity in autism [Green et al, ; Green et al, ; Yang et al, ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scanning was performed on a Siemens MAGNETOM 3 Tesla Tim Trio scanner at the Yale Magnetic Resonance Research Center (for YCSC participants) or a Philips 3 Tesla MR system (for CBH‐UTD participants) within 1 week before and after the treatment. Details regarding the imaging parameters and individual‐level processing steps had been described in previous research [Yang et al, ,b). The participant‐level contrast of interest is BIO > SCR, which served as inputs for the subsequent mass univariate fMRI analyses.…”
Section: Methodsmentioning
confidence: 99%
“…We measured the pretreatment and posttreatment BOLD (blood oxygen level dependent) responses using a well-established biological motion fMRI task [Bjornsdotter, Wang, Pelphrey, & Kaiser, 2016;Kaiser et al, 2010;Ventola et al, 2015;Yang et al, 2016Yang et al, , 2017a. We selected this paradigm because it measures the neural activities of two key components of social information processing [Kaiser et al, 2010], namely, socioemotional and socio-cognitive processing, which correspond to the treatment targets of VR-SCT and the two behavioral measures of emotion recognition and theory of mind, respectively.…”
Section: Fmri Imaging Taskmentioning
confidence: 99%